Affective discrimination methodology: Determination and use of a consumer-relevant sensory difference for food quality maintenance. (April 2015) - Kim, Min-A; Sim, Hye-Min; Lee, Hye-Seong
Abstract: To achieve more efficient decision making for many business objectives including reformulations and processing changes in the food industry, the important questions become 1) what is the best way to measure consumer discrimination and 2) how much discrimination is meaningful in consumer preference that can be used as a business action standard for food quality maintenance. The purpose of the present paper was to develop a consumer sensory discrimination methodology using affective reference framing to provide more accurate information on both questions. For such affective methods, two versions of repeated duo–trio tests using the preferred sample as reference were implemented: Affective group I—each of 8 repeated duo–trio tests was preceded by a paired-preference test; and Affective group II—a paired-preference test was performed before each of the two sub-sessions consisted of 6 repeated duo–trio tests and the preferred sample was used as a constant-reference during the sub-session. The discrimination performance of these tests was compared to the analytical balanced-reference duo–trio test. Results indicated that for affective group I only, it was possible to identify the 'affective discriminators' who showed genuine preference for one product over another and their sensory discrimination in the affective method was significantly higher than in the analytical method. It suggested that this affective method is a desirable consumer sensory methodology that can reveal insightful consumer-relevant sensory differences by comparing sensory discriminations between the so-called 'affective discriminators' and 'affective non-discriminators'. Highlights: New approach to study consumer segmentation on sensory preference was invented. This used repeated preferred-reference duo–trio test with paired-preference test. Individual preference data was used to identify consumer segment who had preference. This segment (defined as affective discriminators) better performed the duo–trio. Their magnitude of sensory discrimination can be used as business action standard.